Heat Stable α- and Glucoamylase Performing Deep Enzymatic Hydrolysis of Starch to Fermentable Glucose - Rusudan Khvedelidze; Lali Kutateladze; Tinatin Sadunishvili; Nino Zakariashvili; Zurab Darbaidze; Tina Aleksidze (European Scientific Journal, ESJ, 2019)
The temperature optimum for thermophilic strains, selected α-amylase producers has been studied in the cultural liquids obtained after their submerged cultivation in the temperature range 30-45°C, at 5 °C intervals. The temperature optimum of the strains was established to be within the range 68- 72 °C, making possible to use them in bio- and enzymatic technologies to diminish the pollution of the reaction medium while conducting the fermentation process at pasteurization temperature (65 °C). Consequently, the selection of stable, operable at pasteurization and higher temperatures amylase preparation is of great importance. Proposed technology is cost-effective, ecologically safe and competitive and provides deep hydrolysis of starch to fermentable sugar at the elevated temperature (68-72 °C) in one-step, by means of only one, stable amylase preparation. Exhaustive hydrolysis process of starch solutions of different concentrations (15, 30, and 40 %) with cultural liquid and technical preparation of Aspergillus niger p8-3 enzyme was studied. In case of low concentrations exhaustive hydrolysis of starch lasts 40-60 minutes, in case of high concentrations hydrolysis takes longer time. 98,6% Yield of glucose can be reached at incubation during 12 hours with enzyme cultural liquid and 8 hours incubationwith technical preparation of the enzyme at gradual increase of temperature from 50°C to 82°C during the first 20 minutes and further decrease of temperature to 70°C. Temperature setting for high yield of glucose and high hydrolysis (pasteurizing), optimal for activity of these strains is the prerequisite to be able to carry out hydrolysis of starch to glucose in one step, and, consequently, using one strain, what will be economically justified.